Artificial Neural Network Based Byzantine Agreement Protocol - Lee, Kok Wah (2002)
The dependability of a distributed system is based on its reliability and availability , which are the fault-tolerant capabilities of a system in handling malfunctioning components and masking malicious faults. The spread of malevolent faults and software errors within the distributed systems and internet networks create a faulty situation where the faulty components will behave arbitrarily. In this thesis, an innovative and improved protocol to solve the BGP using the artificial neural network is proposed.